Kombinasi Penerapan Rendaman Kaki Air Hangat dan Foot Massage Roller Terhadap Tekanan Darah Penderita Hipertensi - RETNO KIKI SAFITRI; NOVA NURWINDA SARI; SUJIAH (Hang Tuah Medical Journal, 2026)
Hypertension is a common health problem in adults and can lead to serious complications if not properly managed. At UPTD PSLU Tresna Werdha Natar, cases have increased over the past three years. Current management relies mainly on pharmacological therapy, while non-pharmacological interventions such as warm foot soaking and foot massage rollers have not been implemented. This study aimed to determine the effect of combining warm foot soaking and foot massage rollers on blood pressure in hypertensive patients at UPTD PSLU Tresna Werdha Natar, South Lampung, in 2025. This study used a quantitative pre-experimental design with a one-group pretest-posttest approach. A total of 17 respondents were selected using purposive sampling. The intervention consisted of warm foot soaking combined with a foot massage roller, administered three times per week for two weeks. Data were analyzed using the paired sample t-test. Most respondents were female (64.7%) and aged 60–70 years (58.8%). Before the intervention, the majority had stage 2 hypertension (76.5%). After the intervention, blood pressure decreased among respondents. The paired sample t-test showed a p-value of 0.000 (p < 0.05), indicating a significant effect of the combined intervention on reducing blood pressure. These findings suggest that this combination can be applied as a non-pharmacological intervention to help control blood pressure in elderly patients with hypertension.